Short Antimicrobial Peptides and Peptide Scaffolds as Promising Antibacterial Agents - Domalaon, Ronald; G. Zhanel, George; Schweizer, Frank (Current Topics in Medicinal Chemistry, 2016)
Antimicrobial peptides have recently garnered significant attention as an emerging source of potential antibiotics, due to the swift emergence of multidrug-resistant bacteria and a dwindling antibiotic pipeline. The vast majority of antimicrobial peptides are long, comprised of more than 10 amino acids, resulting in significant production costs for their synthesis while simultaneously displaying metabolic instability and relatively poor pharmacological profiles. To counter these problems, efforts have been shifted to shorter molecules and the development of new peptidomimetic approaches. In this paper, we review promising short, naturally-isolated or synthetic, antimicrobial peptides, along with their mimics, and discuss their merits as potential antibacterial agents.
Keywords: Bacterial resistance